2 ANTI-TANK REGIMENT, SAA -TANK AND ANTI-TANK IN THE WESTERN DESERT, 1940-1942 (PART IV) - Richard Cornwell (Scientia Militaria, 2012)
MovIng into the Gazala Line By the end of January Rommel's counter-attack had put him in possession of Benghazi, while XIII Corps attempted to make the best of a fighting retreat eastwards across the Jebel. The Axis forces' petrol difficulties had convinced Rommel that he would have to halt the main body of his advancing troops in the Benghazi area, although Afrika Korps might be pushed forward to the vicinity of Gazala. Meanwhile Ritchie, commanding 8 Army, at last believed his subordinates' protestations that they were at present unable to successfully oppose any enemy armoured force and agreed to a withdrawal to a line running from Gazala to Bir Hacheim.